Birth Order, Family Size, and Achievement: Family Structure and Wage Determination - Kessler, Daniel (Journal of Labor Economics, 1991)
The influence of birth order and childhood family size on future achievement is discussed. Two major empirical findings are presented by the author. "First, neither birth order nor childhood family size significantly influences the level or growth rate of wages, a result that is consistent with previous research. Second, family size is both a statistically and economically significant determinant of women's employment status: women from small families work less than women from large families when they are young and more than women from large families when they are more mature." The geographical focus is on the United States.